The role of the National Land Agency As a Mediator Settlement Land Disputes (A Study at the National Land Agency Office, Kendari City) - Imadul Hafidz, Muh. Iswandi; Khayati, Sri; Alimuddin, Alimuddin (International Journal of Management and Education in Human Development, 2025)
As for the purpose of the study, This is for knowledge. How does the mechanism work? settlement of land disputes through mediation at the Land Office vehicle 2. How does the Kendari National Land Agency (BPN) function as a mediator in land settlement disputes?. The study employs a juridical empirical method, which involves studying not only the positive aspects of law but also its implementation or field practice. The data analysis technique used is descriptive qualitative, namely after the data is collected, then poured into alogical and systematic form description, then analyzed to acquire clarity on the settlement problem, then withdrawn as a conclusion in a deductive way, namely from things that are general going to things that are special. Based on research, obtained results: 1. The way the Land Office handles land disputes through mediation follows the rules set by the Decree of the Head of the National Land Agency of the Republic of Indonesia Number 34 of 2007, which outlines how to deal with land problems, but the outcomes are not as good as they could be. 2. Efforts made by the Land Agency include assisting the parties in understanding each other's views and helping them look for things that are considered important for them. The mediator makes it easier to exchange information and encourages discussion about different interests, perceptions, and interpretations of situations and issues. The mediator helps the parties prioritize issues and emphasize discussion about general goals and interests. The mediator will often meet with the parties in a personal way. As a receptacle for information between the parties, the mediator will have more Lots of information about disputes and issues compared to the parties, and will be capable of determining whether there is a basis for realizing something, an agreement, or adequate technical instruction so that no There is doubt again for the apparatus implementer. For running it.